(untitled) (Journal of Educational Sciences, 2022)
The transition to competence-oriented educational standards of higher education involves the development of professional competences for successful professional activity among students. The purpose of the research is to study and analyze the experience of the development of professional competences in the training of pre-service social educators in Kazakhstan and Lithuania. A comparative descriptive analysis was used, research data collected during the analysis of the literature review and regulatory documents, educational programs for the preparation of bachelors in social pedagogy are presented. While studying at the university under the educational program "Social Pedagogy and self-cognition", in our opinion, an integral system of professional competences should be developed for working in an inclusive education. The nature and trends of the training of social educators in two countries are revealed, the general and special features in the process of developing the competences of social educators and the need to focus on professional competences adopted by the world community are identified. Analysis of the normative documents of the Republic of Lithuania showed that the training of future social educators, the development of its competencies is in a specialized direction and involves the preparation of social educators to work in an inclusive education. It is facilitated by the teaching of the following disciplines: "Education about children’s health", "The work of a social educator", "Protection of children’s rights", etc. Keywords: inclusive education; professional competences; descriptive, comparative analyses; social pedagogy.